Interleukin-4 Ameliorates the Functional Recovery of Intracerebral Hemorrhage Through the Alternative Activation of Microglia/Macrophage - Yang, Jianjing; Ding, Saidan; Huang, Weilong; Hu, Jiangnan; Huang, Shengwei; Zhang, Yu; Zhuge, Qichuan (Frontiers in Neuroscience, 2016)
Neuro-inflammation plays an important role in the recovery of brain injury after stroke. Microglia/macrophage is the major executor in the neuro-inflammation, which can be polarized into two distinct phenotypes: injurious/toxic classical activation (M1 phenotype) and protective alternative activation (M2 phenotype). Here, we investigated whether intracerebral administration of interleukin-4 (IL-4) at an early stage could affect the activation of microglia/macrophage and the corresponding outcome after intracerebral hemorrhage (ICH). The neuro-behavior was recorded between different groups in the rat ICH model. The M1 and M2 markers were then determined by qRT-PCR, western blotting, ELISA and immunofluorescence, respectively. We observed aberrant activation of microglia/macrophage after ICH. After intracerebral injection of IL-4, M1 activation was greatly inhibited while M2 activation was enhanced, along with improving neurobehavioral recovery from deficits after ICH. Our study showed that early intracerebral injection of IL-4 potentially promotes neuro-functional recovery, probably through enhancing the alternative activation of microglia/macrophage.